Design and Development of a Management Platform for the ADE (Algérienne Des Eaux) Public Establishment - قمولهّ, رجاء; تومي, علياء; سعدين, أمةالله رحمة (Université of Eloued جامعة الوادي, 2026)
Managing daily water consumption is among the vital challenges facing public institutions, especially in light of increasing demand and the need to ensure quality service to citizens. From this perspective, this memorandum presents a practical vision for a smart digital platform, including a mobile application and a web page, with the aim of improving the administrative management of the Algerian Water Corporation (ADE) and facilitating interactions between the company and citizens. The project focuses on digitizing a number of traditional services, such as viewing water consumption, tracking bills, filing complaints, and scheduling debts, while also providing a smart notification system for users. The platform also engages multiple stakeholders, most notably customers and company employees. The system was designed flexibly to ensure full functionality is available based on the authority of each category. This project aims to be an effective digital nucleus for bringing public services closer to citizens and enhancing the efficiency of work within the institution. It also opens up future prospects for expanding the platform to include other smart services that support the digital transformation in the water sector. الطلب وتحقيق جودة الخدمة للمواطن. ومن هذا المنطلق، جاءت هذه المذكرة لتقديم تصور فعلي لمنصة رقمية ً ذكية تشمل ا للهاتف وصفحة ويب تطبيق ، بهدف تحسين التسيير اإلداري لمؤسسة الج ازئرية للمياه ADE، وتسهيل العمليات التفاعلية بينها وبين المواطنين. يرّكز المشروع على رقمنة عدد من الخدمات التقليدية، مثل االطالع على استهالك المياه، تتبع الفواتير، تقديم الشكاوى، وجدولة الديون، مع توفير نظام تنبيهات ذكي للمستخدمين. كما يتفاعل من خالل المنصة عدة فاعلين، أبرزهم: الزبون و موظف الشركة، ا حيث تم تصميم النظام بشكل مرن يضمن االستفادة من كافة الوظائف وفق لصالحيات كل فئة. يسعى هذا المشروع إلى أن يكون نواة رقمية فعالة لتقريب الخدمة العمومية من المواطن، ورفع كفاءة العمل داخل ل الرقمي في قطاع المياه ا مستقبلية لتوسيع المنصة نحو خدمات ذكية أخرى تدعم التحو المؤسسة، كما يفتح آفاق
مذكرة تخرج سنة ثالثة ليسانس إعلام آلي
Keywords: Water company; شركة مياه